Іnformation support of automated technology of computer-integrated control of building heating - Olishevskyi I. H.; Titov M. G. (НТУ "ДП", 2024)
The development and implementation of automated technologies for controlling heat pump systems, including during the computer-integrated control of the building heating process, allows optimizing the use of energy and resources, as was proved in the second chapter of this dissertation. In turn, the information provision of such technologies allows for accurate zonal control and regulation of temperature in premises and buildings, which optimizes energy consumption and, accordingly, minimizes heating costs. The basis of the developed information support technology for the automated control of building heating using the proposed computer-integrated method of increasing the energy efficiency of the heat pump heating system is based on a model that includes the following procedures and functions.
Keywords: комп’ютерно- інтегровано управління; опалення будівлі; автоматизовані технології